Multi-method geophysical mapping of ground properties and periglacial geomorphology in Hans Glacier forefield, SW Spitsbergen - Marciniak, Artur; Osuch, Marzena; Wawrzyniak, Tomasz; Owoc, Bartosz; Dobiński, Wojciech; Glazer, Michał; Majdański, Mariusz (Polish Polar Research, 2022)
This article presents the results of a geophysical survey from which detailed images of glacial and periglacial landforms and subsurface structures were obtained. Sediments and landforms on newly deglaciated terrain can be used to reconstruct the extent and character of glaciers in the past and add to the understanding of their response to climate and environmental changes. To derive spatial information from complex geomorphological terrain, joint interpretation of three non-intrusive geophysical methods were applied: Electrical Resistivity Tomography (ERT), Ground Penetrating Radar (GPR), and time-lapse Seismic Tomography. These were used to identify subsurface structures in the forefield of the retreating Hans Glacier in SW Spitsbergen, Svalbard. Three main zones were distinguished and described: outwash plain, terminal moraine from the last glacial maximum, and glacial forefield proximal to the glacier front. Geophysical profiles across these zones reveal information on glacio-fluvial sediment thickness and structure, ice thickness and structure, and bedrock topography. The freezing-thawing effect of the active layer has a strong and deep impact, as demonstrated by variations in P-wave velocity in the obtained outcomes. The results are discussed in the context of the current climate in Svalbard. This study provides a snapshot of ground parameters and the current state of the subsurface in southern Spitsbergen. The boundary between sediment-bedrock layers was estimated to be from 5 to 20 m in depth. It is the first such extensive description of periglacial structures in the forefield of the Hans Glacier, utilising the longest ERT profile (1500 m) in Svalbard together with deep GPR and precise seismic tomography.